Broad spectrum anti-infective properties of benzisothiazolones and the parallels in their anti-bacterial and anti-fungal effects. Issue 5 (1st March 2017) - Gopinath, P.; Yadav, R.K.; Shukla, P.K.; Srivastava, K.; Puri, S.K.; Muraleedharan, K.M.
Graphical abstract: Abstract: Various mono- and bis -benzisothiazolone derivatives were synthesized and screened against different strains of bacteria and fungi in order to understand the effect of multiple electrophilic sulfur atoms and substitution pattern in the immediate vicinity of reactive sulfur. Staphyllococcus aureus -ATCC 7000699, MRSA and S. aureus -ATCC 29213 (Quality Control strain) were more susceptible to this class of compounds, and the most potent derivative1.15 had MIC50 of 0.4 μg/mL (cf. Gentamicin = 0.78 μg/mL). CLogP value, optimally in the range of 2.5–3.5, appeared to contribute more to the activity than the steric and electronic effects of groups attached at nitrogen. By and large, their anti-fungal activities also followed a similar trend with respect to the structure and CLogP values. The best potency of IC50  = 0.1 μg/mL was shown by N-benzyl derivative (1.7 ) against Aspergillus fumigatus ; it was also potent against Candida albicans, Cryptococcus neoformans, Sporothrix schenckii, and Candida parapsilosis with IC50 values ranging from 0.4 to 1.3 μg/mL. Preliminary studies also showed that this class of compounds have the ability to target malaria parasite with IC50 values in low micromolar range, and improvement of selectivity is possible through structure optimization.